Pengaruh Perbedaan Gaya Belajar dan Keikutsertaan Organisasi Terhadap Pemahaman Hasil Pembelajaran Mahasiswa - Nia Savira Febrianti (ScienceEdu: Jurnal Pendidikan IPA, 2019)
This article is made based on the diversity of different learning styles and student interest in talent, especially participation in organizational activities. This article was made with the aim to find out the different learning styles for each student and the participation of organizational activities and their influence in gaining understanding and learning outcomes. The differences in learning styles and talent interests of each student are abilities in themselves. Teachers can also play a role in helping understanding learning in each individual who has different learning styles and interests. In this article it can be seen that organizational activities have positive and negative influences in learning and learning outcomes. The writing of this article uses the literature study method, by looking at various sources or references, such as books or several other journals concerning the same material as the article I made. With this article, it can be taken as a reference in learning. Thus, learning goals can be achieved without having to put pressure on students. Kata Kunci: learning style, interest in talent, organizational activities, understanding of learning